Beta-blockers utilization in heart failure patients: Sub-analysis of a nation-wide population-based study in the Czech Republic - Táborský, Miloš; Aiglová, Renáta; Lazarová, Marie; Pavlů, Luděk; Daněk, Josef; Přeček, Jan; Schee, Alexandr; Gloger, Vít; Vícha, Marek; Skála, Tomáš (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2021)
AIMS: Sub-analysis of a retrospective nation-wide observational analysis of heart failure (HF) epidemiology reported to the Czech National Registry of Reimbursed Health Services between 2012 and 2018 aimed at beta-blockers (BBs) utilization. METHODS AND RESULTS: The beta-blockers were generally used in 81.8% of all patients treated for HF in 2012 (n=52 140); 81.8% in 2013 (n=53 058); 83.1% in 2014 (n=56 221); 82.1% in 2015 (n=57 421); 83.3% in 2016 (n=59 187); 82.2% in 2017 (60 058) and in 81.4% in 2018 (n=60 966). In 2018, the majority of patients treated for HF were prescribed metoprolol (22 974; 30.7%) and bisoprolol (21 001; 28%). Carvedilol was prescribed in 7 331 patients treated for HF (9.8%), nebivolol in 5 392 HF patients. Despite its primary indication, betaxolol was used in 2 341 patients treated for HF (3.1%). All other beta-blockers were used in less than 1% of HF patients. In some of the mostly used BBs, their prescription in patients treated for HF changed in the last years (metoprolol 32.4% in 2012, 30.7% in 2018; bisoprolol 20.3% in 2012, 28% in 2018; carvedilol 18.3% in 2012, 9.8% in 2018; nebivolol 2.5% in 2012, 7.2% in 2018; betaxolol 4.2% in 2012, 3.1% in 2018). CONCLUSION: In an analysis of beta-blockers utilization in all patients treated for heart failure in the given year in the whole country, we have found only slightly lower amount of drug prescription in comparison with specific heart failure registries. This indicates a good translation of current standard of care into common clinical practice. Metoprolol remained the mostly prescribed drug. The prescription of bisoprolol and nebivolol has increased at the expense of carvedilol.
Keywords: Carbazoles; nebivolol; bisoprolol; Carvedilol; beta blokátory; karbazoly; karvedilol; propanolaminy; Heart Failure; betaxolol; Propanolamines; lidé; srdeční selhání; Betaxolol; Nebivolol; Metoprolol; retrospektivní studie; Bisoprolol; Czech Republic; metoprolol; Česká republika; Adrenergic beta-Antagonists; Retrospective Studies; Humans